IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERWAWASAN MULTIKULTURAL DI SMP NEGERI 1 MEMPAWAH TIMUR KABUPATEN MEMPAWAH - Agustiar, Syarif; Ubabudin, Ubabudin; Jaelani, Jaelani (ILJ: Islamic Learning Journal, 2024)
The learning of Islamic religious education at SMPN 1 Mempawah Timur has shown the concept of multicultural insight both in terms of the understanding of Islamic religious education teachers and the various materials taught which are then integrated with multicultural behaviours. The approach used in this research is a qualitative approach, while the type of research used by researchers is a case study, which is a research conducted intensively, in detail and in depth to an organisation, institution or certain symptoms. The results of this study show that the learning model of multicultural-based Islamic Religious Education at SMP Negeri 1 Mempawah Timur uses local wisdom. Supporting factors and inhibiting factors in the implementation of Islamic Religious Education at SMP Negeri 1 Mempawah Timur. Supporting factors of multicultural-based Islamic Religious Education Learning in SMP Negeri 1 Mempawah Timur are: a) Principal's policy b) Qualified teacher resources, c) Students have a strong basic understanding of religion so that they do not question the differences. While the inhibiting factors of multicultural-based Islamic Religious Education learning are a) lack of parental awareness due to limited education so that they tend to have excessive fanaticism. b) environmental factors that do not support because they are not ready to accept differences. c) the lack of references about multicultural owned by SMP Negeri 1 Mempawah Timur